The expression of multidrug resistance protein 5 and thymydilate synthase on fluorouracil resistance WiDr colon cancer cell line - Yolanda Dyah Kartika; Indwiani Astuti; Woro Rukmi Pratiwi (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2015)
Background: Colorectal cancer becomes one of the most common cancer in Indonesia. Fluorouracil is an essential drug in colorectal cancer therapy as it has been supplemented in about 69% of current regiments of chemotherapy. However, drug resistance has reduced its clinical applications. Many factors that contribute to fluorouracil resistance have been investigated including overexpression of Multidrug Resistance Protein 5 (MRP 5) and high level expression of Thymidylate Synthase (TS). Therefore, the expression of those proteins may become key indicators to predict the presence of resistance in the model of fluorouracil-resistance-WiDr colon cancer cell line. Objective: The aim of this study is to characterize a 5-FU acquired resistance WiDr colon cancer cell line, focus on the expression of MRP5 and TS. Methods: This study was a post test controlled group design. The expression of MRP5 and TS were analyzed using immunocytochemistry method. Before protein expression analysis, 4 groups of WiDr colon cancer cell line, group 1, 2, 3, and 4 (control) were treated with 4 different concentration of fluorouracil 12.3 μM, 6.15 μM, 3.08 μM, and 0 μM respectively. Previous study showed that a significant increased level of IC50 value is observed in group induced with fluorouracil 3.08 μM (group 3). Statistical tests for protein expression performed with SPSS version 19 using Kruskall Wallis with 95% confidence level (p<0.05). Results: The expression of MRP5 and TS in the group developed fluorouracil resistance (group 3) were significantly increased compared to control group (p<0.05). In contrast, the other group exposed with higher dose of fluorouracil did not show both significant increased level of IC50 nor significant different of MRP5 and TS expression compared with the control group. Conclusion: The model of fluorouracil-acquired resistant WiDr cell line expresses Thymidilate Synthase and Multidrug Resistance Protein 5. The expressions of these proteins are in accordance with the profile of fluorouracil resistancy.